Toward a Bold Agenda for Moral Education - Chinnery, Ann (Philosophical Inquiry in Education)

(untitled) (Canadian Philosophy of Education Society, 2019)
In his 2006 essay, “Moral Education’s Modest Agenda,” Robin Barrow argues for a clearly bounded conception of morality; he presents the moral domain as concerned with moral principles, and moral education as the cultivation of moral understanding. Barrow rejects behaviourism, character education, values clarification, developmentalism, and what he calls “the insidious influence of political and moral correctness” as practices and ideas that are irrelevant and inappropriate for moral education. While I share some of Barrow’s concerns about some of these approaches, I believe he over-restricts the scope of legitimately moral concerns and what educators ought to do in the name of moral education. In this paper, I make a case for a broader and bolder agenda for moral education, putting the question of what constitutes a human life (which Barrow takes to be a non-moral question) at the very heart of morality and moral education.